Challenges in Learning Argumentative Texts among Indonesian Vocational School Students: An Analysis of Language and Cognitive Barriers - Danendra, Azriel Daffa; Basya, Dihliza; Nugraheni, Dyah Ayu (IAIN KENDARI, 2026)
The skills of argumentative writing depend on the writer's mastery of language and their ability to use higher-order thinking. The students in this study are from a vocational high school, where they do not have many opportunities to write longer, more formal essays, such as those required for a university-level composition course, so this study looked at the cognitive and linguistic barriers experienced by those students when writing argumentative essays. At a vocational high school located in Jember, East Java, Indonesia, 35 twelfth-grade accounting students participated in this study using a mixed-methods approach. Data collection included classroom documentation; a questionnaire on a Likert scale; and an analysis of the students' written argumentative essays. The questionnaire assessed cognitive barriers to argumentative writing - critical thinking, metacognitive awareness, and organization of arguments - and the document analysis identified linguistic barriers in the students' writing related to vocabulary, grammar, and cohesion using a standard five-point scoring rubric. The findings revealed moderate linguistic barriers in vocabulary (M = 3.14) and grammar (M = 2.83), whereas cohesion obtained the lowest score (M = 2.59). In terms of cognitive barriers, students demonstrated moderate levels of critical thinking and argument organization, while metacognitive awareness was relatively high. These findings indicate that both linguistic and cognitive factors influence students’ ability to produce effective argumentative texts. Therefore, instructional strategies that address language development and cognitive skills are needed to support students’ argumentative writing performance.